Interrelated Treaty Orders Across the Generations: Autonomy, Obligation and Confederacy in the Wabanaki Compact (1725-26) - Costa, Andrew (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2018)
Throughout the 18thcentury, the eastern Wabanakipeoples and the British Crown negotiated several Peace and Friendship Treaties, as well as Compacts, to properly situate the Crown among the WabankiConfederacy (Mi’kmaq, Penobscot, Wulstukwiuk, Passamaqoddy). One treaty was the Wabanaki Compactof 1725-26. The agreements that comprised the Wabanaki Compactwere negotiated in the years succeeding the Treaty of Utrecht (1713) and the Indigenous - Crown skirmishes and raids that culminated in Dummer’s War (1722 – 25). This paper asserts the Wabanaki Compact(specifically Mascarene’s Treaty) maintains legal import by showing that many components of the agreement actually contained Crown obligation to preserve customary religious observance and generational hunting, fishing and trapping rights. The Compact also builds up interdependent relations between the Crown and the Wabanakithat were premised on a strong responsibility to preserve and assist the well being of adjoined communities or nations.These assertions will be analyzed through the lens of Wabanaki legal teaching related to interrelatedness, generational obligation, linguistic protocols and gift giving ceremonies. Legal judgments like R v. Sappier & Polchiesand R v. Sappier; R v. Greyshow that the Crown is tied to these relations by recognizing their role in affirming their fidelity to the treaty order well into the future. Analyzing the Compactwith these principles in mind implies that partners individually hold normative autonomy while also collectively holding obligation to preserve living treaty partnerships throughout future generations.It is argued that theWabanaki Compactalsoretains legal relevance by tying the Crown and the Wabanaki(specifically the Mi’kmaqand Wulstukwiuk) in intergenerational obligation through respecting and preserving the autonomy which brought them to the Compactin the first place.